Migration and the European convention on human rights - Çalı, Başak; Bianku, Ledi; Motoc, Iulia (Oxford University Press, 2021)
This book investigates where the European Convention on Human Rights (ECHR) as a living instrument stands on migration and rights of migrants. Individual chapters in the volume address how the tension between the textual silence of the Convention concerning migrant rights and the significant number of cases that the ECHR have addressed concerning migration and rights migrants are resolved or left to the discretion of European states. This book offers a comprehensive analysis of cases brought by migrants in different stages of migration covering the right to flee, who is entitled to enter and remain Europe, what treatment is owed to them when they come within the jurisdiction of a Council of Europe member state, not only to those who recently entered Europe, but also to those who have been living in Europe for a longer time. As such, the book evaluates the case law of the ECHR concerning different categories of migrants including asylum seekers, irregular migrants, those who have migrated through domestic lawful routes and those who are currently second- or third-generation migrants in Europe. The broad perspective adopted by the book allows for a systematic analysis of how and to what extent the Convention protects non-refoulement, migrant children, family rights of migrants, status rights of migrants, economic and social rights of migrants, as well as cultural and religious rights of migrants.
CRIS-Team Scopus Importer:2023-03-21
Keywords: ECHR; International human rights law; International law; Migrants; Migration